Kobiety Świadkowie Jehowy w nazistowskich obozach koncentracyjnych. Przyczynek do charakterystyki społeczności kobiecych w lagrach - Czarnecka, Barbara (Narracje o Zagładzie [czasopismo zamknięte], 2020)
The article describes Jehovah’s Witnesses women as one of less remembered groups among victims of the Nazi regime. What is pointed out, first of all, is the state of research on their history, especially pertaining to their camp experience, Western literature on the subject and a negligible number of Polish research works devoted to the topic in question, and also some methodological dilemmas related to researching it. The author presents the circumstances of German Jehovah’s Witnesses after Hitler’s seizure of power, their subsequent persecutions, and also – reconstructed on the basis of documents, witnesses reports, and the members of persecuted group themselves – the fate of female followers of this religion (“the purple triangles”) in concentration camps. The author’s main points of focus are, described by witnesses/beholders/onlookers of the events, acts and attitudes of “the purple triangles” marked by strong spirituality, at the same time unbreakable/intransigent in their defiance of/against violence and the authorities’ orders. (Everybody knew that Jehovah’s Witnesses could have basically “sign off” from the camp by putting their signature at the bottom of a declaration that they would renounce their faith and cease to practise their religion.) Such a defiance may be better understood, the author claims, by interpreting it in the light of the anthropological concept of emotional communities.